3β-HSD ACTIVATES DHEA IN THE SONGBIRD BRAIN - Schlinger, Barney A. (2007)
Dehydroepiandrosterone (DHEA) is an abundant circulating prohormone in humans, with a variety of reported actions on central and peripheral tissues. Despite its abundance, the functions of DHEA are relatively unknown because common animal models (laboratory rats and mice) have very low DHEA levels in the blood. Over the past decade, we have obtained considerable evidence from avian studies demonstrating that (1) DHEA is an important circulating prohormone in songbirds and (2) the enzyme 3β-hydroxysteroid dehydrogenase/isomerase (3β-HSD), responsible for converting DHEA into a more active androgen, is expressed at high levels in the songbird brain. Here, we first review biochemical and molecular studies demonstrating the widespread activity and expression of 3β-HSD in the adult and developing songbird brain. Studies examining neural 3β-HSD activity show effects of sex, stress, and season that are region-specific. Second, we review studies showing seasonal and stress-related changes in circulating DHEA in captive and wild songbird species. Third, we describe evidence that DHEA treatment can stimulate song behavior and the growth of neural circuits controlling song behavior. Importantly, brain 3β-HSD and aromatase can work in concert to locally metabolize DHEA into active androgens and estrogens, which are critical for controlling behavior and robust adult neuroplasticity in songbirds. DHEA is likely secreted by the avian gonads and/or adrenals, as is the case in humans, but DHEA may also be synthesized de novo in the songbird brain from cholesterol or other precursors. Irrespective of its source, DHEA seems to be an important neurohormone in songbirds, and 3β-HSD is a key enzyme in the songbird brain.